Research of orientation methods of autonomous mobile robots in industrial conditions - Yechevskyi, A. D.; Sotnik, S. V. (ХНУРЕ, 2025)
The work analyzes the main methods of navigation of mobile robots, in particular odometrics, computer vision, artificial markers and tags, lidar, and SLAM. their principles of operation are considered in detail; The advantages and disadvantages of the considered methods of orientation of autonomous mobile robots in industrial conditions are determined. У роботі проведено аналіз основних методів навігації мобільних роботів, зокрема одометричні, комп’ютерного зору, штучних маркерів та міток, лідарів та SLAM. їх Детально розглянуто принципи роботи; визначено переваги та недоліки розглянутих методів орієнтації автономних мобільних роботів у промислових умовах.
Дослідження методів орієнтації автономних мобільних роботів у промислових умовах
Keywords: mobile robot; navigation; artificial intelligence; мобільний робот; навігація